ΣΤΕΦΑΝΙΑ ΚΟΦΙΝΑ, Ἡ μεγάλη βδομάδα τοῦ Πρεζάκη: Από το διήγημα στην κομικ-ή μετάπλαση - Κοφίνα Στεφανία (Σύγκριση/Comparaison/Comparison, 2022)
The Big Week of Prezakis: From the short story to the comic transformation The object of the present study is the transposition of the short story The Big Week of Prezakis by M. Karagatsis into a comic and specifically into a graphic novel, in order to investigate and analyse all the remarkable medial transformations that result from this inter-artistic transposition. The study starts from the structure in each of the two works under consideration, that is the way in which the narrative material is organized to serve the inherent imperatives of the genre in question. The transcription of narrative voice and focus in mediated adaptation is also a research desideratum as well as the multiple artistic realizations of the narrator in the comic idiom. Narrative temporality, as a predominantly graphically represented axis in the world of the comic book, as well as the imaginary soundtrack of the works, with the remarkable effect it is found to exert as a verbal statement in both cases, has also been of interest to the study. Finally, both selected characters in the works and the spaces in which they move were put under the microscope. It should be made clear, however, that this consideration is aware of the heterogeneity of the two media and the different semiotic code that governs each of them. Consequently, it is released from any attempt to identify points of convergence or divergence between the two works if these do not take the study towards interesting interpretative results about the adaptation and the transformations it brings about. After all, every adaptation constitutes a creative "departure" from the source work, and it is through this prism that this paper views the whole inter-artistic project.